Nest attributes influence choice accuracy, but not decision latency in acorn ants - Sheila Shu-Laam Chan; Isaac P. Weinberg; Philip T. Starks; Claire T. Hemingway (PLoS ONE, 2026)
Decision making can have significant fitness consequences across various aspects of animal life. For acorn ants, Temnothorax curvispinosus , choosing a new nest quickly and accurately can affect the survival and fitness of the whole colony. When emigrating, ants consider several nest attributes such as cavity shape, height, and brightness. Ants may benefit from having more attributes differentiating potential nests only if they can quickly and accurately assess all possible attributes and make well-informed decisions. Here, we asked if the number and type of attributes differentiating potential nests affected the accuracy and latency of colony decision-making. We used pair-wise tests, where potential nests differed in one to three attributes, with one nest within the pair considered less optimal. We recorded which nest colonies chose and the time it took to make the decision. We found that accuracy increased with the number of attributes, particularly when nest brightness was manipulated, indicating that increasing the number of attributes may help facilitate nest-site selection. We also found that the degree of difference did not affect the decision-making latency, suggesting that ant colonies searching for a new nest might be constrained temporally when selecting a new nest site.